Understanding Youth Well-Being: A Qualitative Investigation of Lived Experiences and Perceptions (International Journal of Scientific Research in Science and Technology, 2025)
Youth well-being is a complex construct that involves physical, mental, emotional, and social aspects that strongly inﬂuence developmental pathways and life outcomes. This qualitative investigation investigates the lived experiences and meanings of well-being among young people aged between 15-24 years. Using thematic analysis and in-depth interviews, this study proﬁles signiﬁcant factors that add to or subtract from youth well- being, such as family relationships, peer relationships, educational experiences, mental health issues, and socio-economic conditions. The results show that youth think about well-being in a holistic sense, with an accentuation of the interrelated aspects of diƯerent life arenas. The research ﬁlls the existing gap in positive youth development literature and oƯers practical lessons for practitioners, policymakers, and researchers working to promote young people ﬂourishing in today’s world.